ARTIFICIAL INTELLIGENCE: WORK CREATIVITY, PRODUCTIVITY AND JOB SATISFACTION IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Bimaruci Hazrati Havidz, Hazimi; M. Rizky Mahaputra (Dinasti Publisher, 2022)
The development of the times requires all elements to develop, even more so within an organization. Currently, human activities in organizations are nothing more than Artificial Intelligence, which supports all organizational activities and makes work more efficient. With the existence of Artificial Intelligence, it is also expected to be able to increase Work Creativity because it can support the development of ideas for members of the organization. Then Artificial Intelligence will also increase the productivity of organizational members and Job Satisfaction. In this article, the researcher uses a descriptive qualitative method, in which the researcher collects data from trusted sources and processes it into the SPSS application. The results of this study are: 1) Work Creativity related to Artificial Intelligence in the Industrial Revolution Era 4.0, 2) Productivity related to Artificial Intelligence in the Industrial Revolution Era 4.0, 3) Job Satisfaction related to Artificial Intelligence in the Industrial Revolution Era 4.0.